\(2xy+6x-y=9\)
\(\Leftrightarrow x\left(2y+6\right)-y=9\)
\(\Leftrightarrow2x\left(2y+6\right)-2y-6=3\)
\(\Leftrightarrow2x\left(2y+6\right)-\left(2y+6\right)=3\)
\(\Leftrightarrow\left(2x-1\right)\left(2y+6\right)=3\)
\(\Rightarrow2x-1\) và \(2y+6\) là Ư(3)\(=\left(\pm1;\pm3\right)\)
Ta có bảng:
2x-1 | 1 | -1 | 3 | -3 |
2y+6 | 3 | -3 | 1 | -1 |
⇔
x | 1 | 0 | 2 | -1 |
y | \(-\dfrac{3}{2}\) | \(-\dfrac{9}{2}\) | \(\dfrac{5}{2}\) | \(-\dfrac{7}{2}\) |
b)\(2y\left(3x-1\right)+9x-3=7\)
⇔\(2y\left(3x-1\right)+3\left(3x-1\right)=7\)
⇔\(\left(2y+3\right)\left(3x-1\right)=7\)
⇒ 2y+3 và 3x-1 là Ư(7)\(=\left\{\pm1;\pm7\right\}\).rồi bạn tự làm nhé
a) 2xy+6x-y=9
<=> 2x(y+3)-(y+3) = 6
<=> (2x-1)(y+3) = 6
=> 2x-1 = 1 và y+3 =6
hoặc 2x-1 = -1 và y+3 = -6
hoặc 2x-1 = 6 và y+3 = 1
hoặc 2x-1 = -6 và y+3 = -1
hoặc 2x+1 = 2 và y+3 = 3
hoặc 2x+1 =-2 và y+3=-3
hoặc 2x+1= 3 và y+3 = 2
hoặc 2x+1 =-3 và y+3= -2
b) 2y(3x-1)+9x-3=7
<=> 2y(3x-1) +3(3x-1)=7
<=> (2y+3)(3x-1)=7
=> 2y+3 =1 và 3x-1 = 7
hoặc 2y+3 = -1 và 3x-1=-7
hoặc 2y+3= 7 và 3x-1 =1
hoặc 2y+3=-7 và 3x-1=-1